1999
DOI: 10.1161/01.res.84.7.831
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p38 Mitogen-Activated Protein Kinase by Oxidized LDL in Vascular Smooth Muscle Cells

Abstract: Oxidized low-density lipoproteins (oxLDL) have been shown to play a crucial role in atherosclerosis, but the underlying molecular mechanisms have not been fully understood. The present study showed that oxLDL strongly evoked phosphorylation and activation of p38 mitogen-activated protein kinase (MAPK) in rat vascular smooth muscle cells (VSMCs) in concentration- and time-dependent manners, reaching the maximal activation at 100 microg/mL within 5 minutes. The results from immunofluorescence staining also revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…The p38 MAPK pathway can be stimulated by cytokines via G protein-coupled receptors or in response to various stress conditions, such as increase in osmolarity (21) or, as shown here in fibroblasts and by others in other cell types, by LDLs (18,(22)(23)(24)(25). How LDLs activate p38 MAPKs is, however, unclear.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The p38 MAPK pathway can be stimulated by cytokines via G protein-coupled receptors or in response to various stress conditions, such as increase in osmolarity (21) or, as shown here in fibroblasts and by others in other cell types, by LDLs (18,(22)(23)(24)(25). How LDLs activate p38 MAPKs is, however, unclear.…”
Section: Discussionmentioning
confidence: 78%
“…Oxidation may be important for the signaling properties of LDLs (5,18). Using the lipoperoxide method, we found that no oxidation could be detected in our LDL preparations (see Experimental Procedures).…”
Section: Ldls Activate the P38 But Not The Jnk Mapk Pathway In Human mentioning
confidence: 91%
“…In various cell types, including SMCs, multiple signaling pathways can be activated by OxLDL, including a p38 MAPKdependent pathway (11) and an extracellular signal-regulated kinase (ERK)-dependent pathway (19,20). We examined whether these pathways were involved in IGF-1R downregulation by OxLDL, using well-known inhibitors of those pathways.…”
Section: Antioxidants Blocked Oxldl-enhanced Ros Production and Igf-1mentioning
confidence: 99%
“…Mechanisms may include changes in the stimulation of various signal transduction pathways, such as the tumor necrosis factor receptor (9), Fas-Fas ligand (9,10), and mitogen-activated protein kinase (MAPK) and Jun kinase pathways (9,11), and in the generation of reactive oxygen species (ROS) (12). In addition to the activation of proapoptotic signal pathways, interference in cell survival signaling could be involved in OxLDL effects on SMCs.…”
mentioning
confidence: 99%
“…Rat thoracic aortic VSMCs were isolated and cultured by a modification of the procedures described elsewhere [8]. Briefly, under sterile conditions, descending thoracic aorta was resected from rats and washed in D-Hank s balanced salt solution.…”
Section: Animal Models and Preparation Of Aortic Vsmcsmentioning
confidence: 99%